Effects of Neuro-Semantic Reframing on Students’ Emotional Coping - Kibtiyah, Asriana; Jasminto; Muaz, Yusuf Ahmed; Tasya, Dinar Ayu; Mustafida, Fita (LETIGES, 2026)
Academic stress often undermines university students’ emotional coping abilities. This study examines the effectiveness of a neuro-semantics-based cognitive reframing technique in enhancing students’ emotional coping when facing academic stress. A quasi-experimental one-group pre-test–post-test design was used, involving 31 undergraduate students from Universitas Hasyim Asy’ari Tebuireng Jombang who experienced academic stress. Data were collected using the Emotional Coping Scale (ECS) and analysed with paired sample t-tests in SPSS 26.0 to measure changes after the intervention. Results showed a significant improvement in emotional coping abilities after the intervention (p = .000, p < 0.05), indicating that neuro-semantics-based reframing effectively enhanced adaptive emotional regulation and resilience against stress. The study's limitations include a small sample, the absence of a control group, and a short intervention period. Future studies should use larger, more diverse samples and longer-term designs to validate these results. This research provides empirical support for integrating cognitive-behavioural and neuro-semantic frameworks in psychological interventions. It demonstrates how meaning reconstruction and meta-state alignment can foster more profound emotional transformation, offering a novel approach to managing academic stress among students.